Hypertensive Disorders of Pregnancy, Cesarean Delivery, and Severe Maternal Morbidity in an Urban Safety-Net Population. Issue 12 (8th July 2020) - Boulet, Sheree L; Platner, Marissa; Joseph, Naima T; Campbell, Alexa; Williams, Rachel; Stanhope, Kaitlyn K; Jamieson, Denise J
Abstract: Hypertensive disorders of pregnancy (HDP) are a leading cause of severe maternal morbidity (SMM), yet mediation by cesarean delivery is largely unexplored. We investigated the association between HDP and SMM in a cohort of deliveries at a safety-net institution in Atlanta, Georgia, during 2016–2018. Using multivariable generalized linear models, we estimated adjusted risk differences, adjusted risk ratios, and 95% confidence intervals for the association between HDP and SMM. We examined interactions with cesarean delivery and used mediation analysis with 4-way decomposition to estimate excess relative risks. Among 3, 723 deliveries, the SMM rate for women with and without HDP was 124.4 per 1, 000 and 52.0 per 1, 000, respectively. The adjusted risk ratio for the total effect of HDP on SMM was 2.55 (95% confidence interval (CI): 2.15, 3.39). Approximately 55.2% (95% CI: 25.7, 68.5) of excess relative risk was due to neither interaction nor mediation, 24.9% (95% CI: 15.4, 50.0) was due to interaction between HDP and cesarean delivery, 9.6% (95% CI: 3.4, 15.2) was due to mediation, and 10.3% (95% CI: 5.4, 20.3) was due to mediation and interaction. HDP are a potentially modifiable risk factor for SMM; implementing evidence-based interventions for the prevention and treatment of HDP is critical for reducing SMM risk.